EVALUASI RANCANGAN MUTU BETON PADA PEMBANGUNAN GEDUNG DI KALIMANTAN BARAT - Andre Renaldi Prameswara; Dony Dony; Rasiwan Rasiwan; Etty Rabihati (Politeknik Negeri Jakarta, 2022)
Concrete is a significant substance that is frequently employed in infrastructure construction. When manufacturing concrete, a concrete mix, or Design Mix Formula (DMF), must be created to specify the proportions of the materials to achieve the desired concrete quality. Concrete quality is classified based on the compressive strength of the concrete, which value has a significant impact on the DMF produced. One of the factors that can affect the quality of concrete is the fact that the dosage used in making concrete in the field is not in accordance with the existing DMF. This means the quality of the concrete in the field is not in accordance with what was planned, namely the quality of K-300 concretes. This study's objectives are to assess the current DMF and examine the variables influencing concrete quality in the field. To conduct the research, the Pontianak State Polytechnic's Civil Engineering Concrete Laboratory tested aggregates, created DMF, created cube specimens, and tested cube concrete compression tests. As a result, it can be said that one DMF can be used for all these structures because the laboratory results demonstrate that the DMF utilized in the field is consistent with the intended concrete quality, namely K-300 concrete quality. At the age of 28 days, concrete with a slump value of 9 cm had an average compressive strength of 339.882 kg/cm2, or 28.21 MPa. According to the findings of these investigations, the field-related factors cause the quality of the concrete to differ from the planned concrete's quality. Keywords: Concrete, DMF, Quality of Concrete, Testing, Compressive Strength.